Active steering for vehicle system using sliding mode control - Nor Maniha, Abd Ghani (2006)
The objectives of this thesis are to present a modeling and control of a singletrack car model for active steering vehicle system. The sliding mode control strategy will be utilized to overcome various coefficients of road frictions and external disturbances on the system. In order to compensate the disturbances, side slip angles and yaw rate of the vehicle will be observed. The model presented take into account different friction of road coefficients of the system. From the mathematical derivation it is found that the system has fulfilled a matching condition. Extensive computer simulations are performed for various types of disturbances such as crosswind and braking torque. From the simulation results the effect of disturbance attenuation will be observed. The performance of the proposed controller will be compared to the linear quadratic regulator and pole placement techniques. The results showed that the sliding mode control scheme is effectively in attenuating various disturbances for different road coefficients as compared to the LQR and pole placement control schemes. Furthermore, the simulation results also showed that the system is insensitive to the external disturbances and capable to overcome 'late action' by the driver due to sudden disturbance on any road conditions.